In vivo effects on intestinal transit and behavior of the argentinian plant Fuchsia magellanica - Bernal Ochoa, Ana María (2017)
Fuchsia magellanica Lam. (Onagraceae) grows in the cold forest of Patagonic Andes mountains, in Argentina and Chile. It is known as “chilco” and leaves and flowers have been traditionally used by mapuche community to alleviate uterine and intestinal spasms. It was also domesticated in the temperate Pampa region of Buenos Aires [1]. Its pharmacological activities never have been studied, but in previous communications we showed that tinctures of leaves and tinctures of flowers from both regions had antispasmodic effect in ex vivo experiments on intestinal smooth muscle [2] and isolated rat uterine tissue [3]. The mechanism of action evaluated through concentration-response curves was the non-competitive inhibition of both, cholinergic contraction and Ca2+ influx [2,3]. In the phytochemical profile there were detected flavonoids such as quercetine, hiperoside, isoquercitrin, canferol and vitexin. The aim of this work was to evaluate the in vivo effect of tincture of Fuchsia magellanica leaves from Patagonia (Fm-P) and from Buenos Aires (Fm-BA) on the intestinal transit and behavior tests such as open-field and elevated plus-maze. Leaves of plants from Patagonia were collected in the summer of 2014, and leaves of plants from Buenos Aires were collected in the winter of 2013, in both cases leaves were dried at air. Tinctures (T) were prepared by maceration in ethanol 70° and dilluted in saline solution the day of the experiment. Tests were performed in Swiss mice (20-30g weight). The intestinal transit was evaluated by i.p. injection of T 30 min before the oral administration of the osmotic laxative PEG3350, followed after 30 min by 10%carbon-1% CMC in saline. After other 30 min the % of small intestinal length covered by carbon was measured. A negative control with ethanol-saline and a positive control with 5mg/kg atropine were done. The open-field test was performed to measure the number of crossed lines (CL) and rearings (Re) of mice in 5 min versus time. In the plus-maze the time remained and the entrance number in open and closed arms were measured. In both tests 0.5 mg/kg diazepam was used as positive control. The T-Fm-P (73.5mg/kg) reduced the intestinal transit to 28.64 ± 6.83% while atropine reduced it to 15.26 ±6.01% (all p<0.05 vs vehicle), but the T-Fm-BA (62.5mg/kg) changed it to 48.74 ±6.82% (NS vs vehicle of 55.12 ±6.39%) (n = 8). In the open-field test both T reduced CL and Re during the first 30-60 min. However, in the plus-maze neither of T significantly changed the ratio of open/closed arms entrances or time. The tinctures of Fuchsia magellanica showed in vivo inhibition of intestinal transit, in agreement with the ex vivo results, as well as a slight sedative effect but were not anxiolitic.